Antibacterial activity of ethanol extract from Kaempferia galanga L. rhizome against pathogenic bacteria - Santhi, Ni Nyoman Ayu Budhi Erlangga; Widiantara, Komang Rian; Artawan, Dewa Gede Wira Putra; Nanda, I Komang Gede Triyana Wahyu (Pharmacy Reports, 2024)
Bacterial infectious diseases have become a serious global health problem due to the increasing bacterial resistance to antibiotics. This study aimed to evaluate the antibacterial activity of ethanol extract from Kaempferia galanga L. rhizome against pathogenic bacteria. The extract was prepared using 96% ethanol through maceration, yielding 14.86% (w/w) of concentrated extract. Phytochemical screening confirmed the presence of flavonoids, tannins, saponins, terpenoids, and steroids. Antibacterial activity was assessed using the disc diffusion method against Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Pseudomonas aeruginosa. The extract exhibited concentration-dependent antibacterial activity against all tested bacteria, with inhibition zones ranging from 6.08-16.38 mm. The most pronounced effect was observed against S. aureus (16.38 mm) at 100% concentration, followed by B. subtilis (15.27 mm), E. coli (12.78 mm), and P. aeruginosa (10.83 mm). Gram-positive bacteria demonstrated higher susceptibility than Gram-negative bacteria. According to Davis & Stout classification, the antibacterial activity of 100% extract against all test bacteria ranged from moderate to strong. These findings suggest that K. galanga rhizome extract has significant antibacterial potential that supports its traditional use in treating infectious diseases and warrants further investigation for development as a natural antibacterial agent.